AN ANALYSIS OF STUDENTS’ ERROR USING PREPOSITION IN NARRATIVE TEXT AT THE THIRD SEMESTER OF ENGLISH EDUCATION STUDY PROGRAM MUHAMMADIYAH UNIVERSITY OF METRO ACADEMIC YEAR 2015/2016 - Atika Dwiyanti (UAD TEFL International Conference)
The third semester of English Education Study Program is supposed to have been able to use preposition correctly. The objectives of this research are to find out what kind of error do the students make in using prepositions based on Surface Strategy taxonomy when they write narrative text; to find out how often the students make error in using preposition when they write narrative text; to find out what are the reasons of the students to make error in using preposition when they write narrative text.This research is a qualitative research. The data analyzed are based on descriptive analysis, namely collecting the data, analyse the students error, classifying the students errors, describing errors based on their type, classifying the result of interview.This research was conducted at Muhammadiyah University of Metro. The subject is third semester of English Department academic year 2015/2016 with 32 students as participant. The data were collected from writing test and interview. The result of research showed that the highest percentages of the errors belong to addition type (48%). The second percentage is misformation type (29%). Then the third is omission type (21%). Next, the last percentage is misordering (2%). It means that the most committed errors made by the students is addition. The studenst really often made error in using preposition when they write narrative text and the students made error in using preposition when they write narrative text is the students were confuse in using prepositions and they did not understand how to differentiate them.